An explicit study of local ozone budget and NOx-VOCs sensitivity in Shenzhen China. (1st March 2020) - Yu, Dan; Tan, Zhaofeng; Lu, Keding; Ma, Xuefei; Li, Xin; Chen, Shiyi; Zhu, Bo; Lin, Liliang; Li, Yanting; Qiu, Peipei; Yang, Xinping; Liu, Yuhan; et al.
Abstract: In China, a significant reduction in primary pollution has been observed due to the Clean Air Action since 2013, and ozone pollution has become increasingly prominent over the past years. Pearl River Delta (PRD) is one of the most successful regions concerning primary pollution control, while is suffering from severe ozone pollution during autumn. In this study, we present a field campaign in Shenzhen, a megacity in PRD, in October 2018 with measurements of ozone and photochemical precursors. These observational data are helpful to analyze the local ozone budget and its sensitivity to precursors with the help of an observation-based model (RACM2-LIM1). The observed ozone concentration was up to 121 ppbv during a photochemical episode from 1 to 8 October, when intensive ozone formation up to tens of ppbv/h was found. Ozone vertical measurement indicates the fast ozone production is happening throughout the planetary boundary layer (PBL), which is an important source of morning ozone increase resulting in ozone pollution. An explicit case study is performed to reveal the diurnal feature of instantaneous ozone production rate (P(Ox )) and accumulative P(Ox ) based on the O3 -NOx -VOC sensitivity, ROx radical primary production rate (P (ROx )), and LN /Q for three cases including ozone pollution and attainment periods. Results show that nitrogen oxides (NOx = NO + NO2 ) reduction have positive and negative impact on local ozone production from one pollution episode to the other, which indicates the complexity of O3 -precursors sensitivity and difficulty to control ozone pollution in Shenzhen. Finally, comparison among measurements in other campaigns provides additional evidence on local ozone production sensitivity on NOx and anthropogenic volatile organic compounds (AVOCs) with respect to a temporal and spatial change. The NOx reduction in Shenzhen has led to higher ozone production from 2015 to 2018 given the nearly constant VOC. However, the ozone mitigation would be benefit from further NOx reduction in the conditions of 2018. Highlights: Field campaign conducted to investigate O3 formation mechanism in Shenzhen. 121 ppbv of O3 was observed in an episode during the China National Holiday. P(Ox ) reached tens of ppbv/h, sufficient to maintain O3 increase. NOx reduction has led to higher ozone production from 2015 to 2018.